Incidental Detection of Adrenal Myelolipoma: A Case Report and Review of Literature. (20th February 2013) - Nabi, Junaid; Rafiq, Danish; Authoy, Fatema N.; Sofi, Ghulam Nabi
Abstract : Introduction . Adrenal myelolipoma is a rare tumor that is benign in nature, usually asymptomatic, unilateral, and nonsecreting. It is composed of variable mixture of mature adipose tissue and hematopoietic elements and develops within the adrenal gland. With the widespread use of cross-sectional imaging modalities such as ultrasonography and computed tomography, the incidental detection of these tumors is increasing in frequency. Case Presentation . We report a case of adrenal myelolipoma in a 63-year-old Kashmiri male, who presented with pain in the right upper abdomen. Physical examination was unremarkable. Ultrasound abdomen showed the presence of a hyperechoic mass in the right suprarenal region with undefined margins. Contrast-enhanced computed tomography (CECT) scan of abdomen revealed a well-defined, round lesion in the right suprarenal region with heterogeneous attenuation suggesting the possibility of myelolipoma. The patient was subjected to right adrenalectomy and his postoperative course was uneventful. The histopathological evaluation of the mass confirmed the initial diagnosis of adrenal myelolipoma. Conclusion . Although mostly discovered as an "incidentaloma", the diagnosis of adrenal myelolipoma warrants thorough diagnostic study. Imaging techniques such as ultrasonography and CT scans as well as biochemical studies are useful for indicating the best treatment taking into account the size of the mass and possible hormone production. Surgical resection is advocated through extraperitoneal approach as it minimizes postoperative complications and leads to quicker recovery.